Color stability of a bulk-fill composite resin light-cured at different distances - Christine Nagel BACKES; Fabiana Mantovani Gomes FRANÇA; Cecilia Pedroso TURSSI; Flávia Lucisano Botelho do AMARAL; Roberta Tarkany BASTING (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The aim of this in vitro study was to evaluate the color stability of a bulk-fill (Filtek One Bulk Fill, 3M ESPE) and a conventional (Filtek Z350 XT, 3M ESPE) composite resin light-cured at different distances, before and after being submitted to staining with a coffee solution. Sixty specimens of each composite resin were prepared and light-cured at distances of 0, 2 and 4 mm, using a LED light-curing unit (Valo, Ultradent). The specimens were separated (n = 10) for immersion in either distilled water or coffee solution (10 minutes a day for 8 days) to stimulate staining. Color evaluations were performed before and after immersion in the solutions, according to CIELab (△Eab), CIEDE2000 (△E00) and the Whiteness Index for Dentistry (△WID). Kruskal Wallis and Dunn tests, Mann-Whitney tests and Wilcoxon test were applied (α = 5 %). The a* value for conventional composite resin showed a significant increase after immersion in coffee and distilled water (p < 0.05). Both composite resins showed greater b* values when immersed in coffee than in distilled water, with no significant difference among the light-activation distances (p > 0.05). There was no significant difference for L* among the light-activation distances; both resins showed significant decrease in L* after immersion in coffee (p < 0.05). Color change (△Eab, △E00) and difference in whiteness (△WID) were higher for conventional resin when immersed in the coffee solution at all the light-activation distances. Conventional composite resin presented a higher staining value than bulk-fill composite resin, regardless of the light-activation distance.